Use of LEDs for tuning of spectra of indoor luminaires (Invited Paper) - Bizjak, Grega; Kobav, Matej B. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
Not so far ago the two most important characteristics of a light source to be used in indoor lighting were lighting efficiency and colour rendering index. First characteristic allow us to make lighting installation also energy efficient and second one assures that the lighting will be well accepted by the users or at least that the premises will look natural. Although both depend on light source spectra, it was very difficult to adapt spectra of the classical light sources to the needs of users. These changes with the introduction of power LEDs to the interior lighting. Today with use of white and monochromatic LEDs we can tailor spectra of luminaires to our needs. This approach can be used not only to obtain better energy efficiency and colour rendering index but also to adapt the spectra to the "non-visual needs" of users. The paper will show some approaches for the selection of the appropriate LEDs for tuning of spectra and the obtained results with different number of used LEDs in luminaire.
Využití LED pro zlepšení spektra vnitřních svítidel (zvaný příspěvek)
Keywords: indoor luminaires; light emitting diodes - LED; spectrum tuning